Wawasan Al-Qur'An tentang Etos Kerja: Kajian Tafsir Tematik Ayat-Ayat Perintah, Balasan Usaha, dan Keseimbangan Hidup - Reski Eka Putri; Muhammadiyah Amin; Abdul Rahman Sakka (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
This study examines the Qur'anic perspective on work ethic as a normative foundation for shaping productive, honest, and God-oriented work character. The problem addressed is the low productivity among Muslims despite the Qur'an's strong emphasis on diligent work. This library research employs a thematic exegetical approach (maudhu'i), collecting and comprehensively analyzing Qur'anic verses related to work ethic. The findings reveal that the Qur'an views work as integral to humanity's caliphal mission on earth, encompassing principles such as sincerity (ikhlāṣ), honesty (ṣidq), professionalism (itqān), diligence, and balance between worldly and otherworldly affairs. Verses analyzed include QS. At-Taubah: 105 (universal command to work), QS. Al-Jumu'ah: 10 (balance between worship and economy), QS. An-Najm: 39-41 (certainty of reward for effort), QS. Ar-Ra'd: 11 (causality of change), and QS. Al-Qasas: 77 (world-hereafter balance). This study concludes that the Qur'anic concept of work ethic contributes philosophically and practically to developing excellent, integral, and competitive human resources without abandoning spiritual values.